MODEL DESAIN SISTEM PEMBELAJARAN ANALYSIS, DESIGN, DEVELOPMENT, IMPLEMENTATION, EVALUATION (ADDIE) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA DIKLAT STENOGRAFI - MENTARI, DYAH AYU (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
The objectives of this research are to investigate: 1) the students? interest in learning stenography in class, 2) the students? score in Stenography education and training; and 3) the effectiveness of the application of the Instructional System Design ADDIE model to improve the learning result in Stenography education and training of the students in Grade XI AP of State Vocational High School 1 of Karanganyar.This research used the classroom action research method with two cycles, and each cycle consisted of four phases, namely: planning, implementation, observation and interpretation, and analysis and reflection. The objects of the research were the students in Grade XI AP 2 of State Vocational High School 1 of Karanganyar as many as 39 students. The data of the research were gathered through in-depth interview, observation, documentation, and test.The results of the research are as follows: 1) the students? interest in Stenography education and training with interested criteria is as much as 17.95%, and the students? interest in Stenography education and training with very much interested criteria is 82.05%; 2) there is an improvement in the students? learning result in the Stenography education and training through the use of the Instructional System Design ADDIE model. 3) The application of the Instructional System Design ADDIE model is effective of improving the students? learning result. The improvement takes place for the teacher has done several efforts as follows: (1) the teacher has managed the class well; (2) the teacher can analyze the difficulties encountered by the students earlier and is able to deal with them; (3) the teacher has made new innovations in delivering the learning materials of Stenography through the application of the Instructional System Design ADDIE model with individual approach method; and (4) the teacher has done evaluation on the learning process, and has executed improvement for the following learning.Keywords: Instructional system design ADDIE model, learning result, and Stenography.